Inoculation of Bacillus spp. Modulate the soil bacterial communities and available nutrients in the rhizosphere of vetiver plant irrigated with acid mine drainage. (January 2021) - Daraz, Umar; Li, Yang; Sun, Qingye; Zhang, Mingzhu; Ahmad, Iftikhar
Abstract: Acid mine drainage (AMD) is one of an important pollution sources associated with mining activities and often inhibits plant growth. Plant growth promoting bacteria has received extensive attention for enhancing adaptability of plants growing in AMD polluted soils. The present study investigated the effect of plant growth promoting Bacillus spp . (strains UM5, UM10, UM13, UM15 and UM20) to improve vetiver ( Chrysopogon zizanioides L.) adaptability in a soil irrigated with 50% AMD. Bacillus spp. exhibited P-solubilization, IAA and siderophore production. The Bacillus spp. strains UM10 and UM13 significantly increased shoot (4.2–2.5%) and root (3.4–1.9%) biomass in normal and AMD-impacted soil, respectively. Bacillus sp. strain UM20 significantly increased soil AP (379.93 mg/kg) while strain UM13 increased TN (1501.69 mg/kg) and WEON (114.44 mg/kg) than control. Proteobacteria, Chloroflexi, Acidobacteria and Bacteroidetes are the dominant phyla, of which Acidobacteria (12%) and Bacteroidetes (8.5%) were dominated in soil inoculated with Bacillus sp. strain UM20 while Proteobacteria (70%) in AMD soil only. However, the Chao1 and evenness indices were significantly increased in soil inoculated with Bacillus sp. strain UM13. Soil pH, AP and N fractions were positively correlated with the inoculation of bacterial strains UM13 and UM20. Plant growth promoting Bacillus spp. strains UM13 and UM20 were the main contributors to the variations in the rhizosphere bacterial community structure, improving soil available P, TN, WEON, NO3 − -N thus could be a best option to promote C. zizanioides adaptability in AMD-impacted soils. Graphical abstract: Image 1 Highlights: AMD inhibited plant growth and shifted microbial community structure. Bacillus spp. showed P-solubilization, IAA and siderophore production. Bacillus spp. enhanced vetiver adaptability and biomass in AMD-impacted soils. Bacillus spp. diluted AMD impacts by improving soil P, N, & microbial communities.